The Importance of Wasathiyah Islam in Efforts to Maintain National Unity and Integrity - Khosiin, Khamam; Humaidi, M. Nurul (Raudhah Publisher, 2024)
Differences in ethnicity, culture, language, and religion are natural characteristics of any society. However, when these differences are not managed wisely, they can become sources of social friction. Disputes, conflicts, and even wars have often emerged from a failure to recognize and appreciate the richness that diversity brings. This lack of understanding stems from an inability to respect differences, leading to tension and division. One critical factor in preventing such conflicts is the cultivation of a proper understanding of religion, as religion significantly influences human behavior and decision-making in daily life. A correct religious understanding provides individuals with the moral compass needed to navigate complex social interactions, helping to foster mutual respect and tolerance. Therefore, it is essential that both religious understanding and practice be approached with moderation. This concept, often referred to as